Impact General Allocation Of Funds And Economic Growth On Government Expenditure In East Kotawaringin - Retno Febriyastuti Widyawati; Andi Lopa Ginting; Ermatry Hariani (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
This study aims to examine the impact of economic growth and the general allocation of funds on economic growth in East Kotawaringin. The descriptive-quantitative research method was used in this study. Multiple linear regression with the t-test, F-test, and coefficient of determination test was used in this study as an analytical tool. According to the findings of this study, the variables of the general allocation fund significantly impact government expenditures in East Kotawaringin. At the same time, economic growth has no significant impact on government expenditure in East Kotawaringin. Concurrently, the general allocation fund variables and economic development affect the government expenditure variable